Farmyard manure and inorganic fertilization effects on saturated hydraulic conductivity of soil and crop performance in rice (Oryza sativa), wheat (Triticum aestivum) and maize (Zea mays) systems* - RASOOL, REHANA; KUKAL, S S; HIRA, G S (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted to evaluate the effect of EYM and inorganic fertilizers on saturated hydraulic conductivity of soil and crop yields in rice-wheat and maize-wheat cropping systems in a long-term experiment (32 years). The treatments included (T,) farmyard manure @ 20 tonnesha in both the crops, (T,) N alone, (T,) N and P and Ok) N, P and K in addition to (T,) control (without any fertilizers or RM). The N, P and K were applied @ 120, 30 and 30 kgha in ricewheat and 100,50 and 50 kgka in maize-wheat.....